Designing a quality assurance process for quality control of nuclear magnetic resonance metabolomics studies of human blood. (12th December 2022) - Muti, Isabella H.; Gonzalez Sanchez‐Dahl, Matteo; Zhong, Anya B.; Weng, JianXiang; Füzesi, Mark V.; Kivisäkk, Pia; Hyman, Bradley T.; Arnold, Steven E.; Feldman, Adam S.; Mercaldo, Nathaniel D.; Cheng, Leo L.
Abstract: High‐resolution magic angle spinning (HRMAS) nuclear magnetic resonance (NMR)‐based metabolomics has demonstrated its utility in studies of biofluids for various diseases. HRMAS NMR spectroscopy is uniquely well suited for analyzing human blood samples because of the small quantity of samples and minimal preparation required. To develop this methodology into standardized clinical protocols, establishment of the method's quality assurance (QA) and evaluations of its quality control (QC) are critical. This study aims to assess the QA/QC measured from human blood specimens in the form of serum and plasma through within‐subject and between‐subject comparisons, as well as stability and consistency comparisons over several freezing–thawing cycles of sample storage conditions, and most importantly, the agreement of pooled control samples against individual samples. Abstract : This study aims to assess the QA/QC measured from human blood specimens in the form of serum and plasma through within‐subject and between‐subject comparisons, as well as stability and consistency comparisons over several freezing–thawing cycles of sample storage conditions and the agreement of pooled control samples against individual samples.